(untitled) (Revista Científica Estelí, 2021)
This study characterizes the discursive strategies used by teachers to encourage the teaching and learning process. The objective of this study is to identify the speech acts used by teachers in the development of the subject Reading, Writing and Spelling Techniques at the National Autonomous University of Nicaragua (UNAN-Managua). In this research a qualitative methodology was used and a grid or observation guide was implemented as an instrument that takes into account the Discourse Analysis from the interpretative paradigm, therefore, the study focuses on the natural context in the classroom. The results evidenced that the speech acts most used by teachers were the directive ones, specifically, those related to questions in which total, partial and rhetorical questions prevailed, therefore, it is exposed that, although teachers evaluate by means of questions, these do not promote a fluid or bilateral communication, since they are questions that are formulated at the superficial level of learning due to the closed answers generated by these questions. In general terms, it is concluded that the types of speech acts used by teachers have a significant impact on the teaching and learning process.